A correlation between the number of satellites and the bulge-to-total baryonic mass ratio extending beyond the Local Group. (10th January 2020) - Javanmardi, Behnam; Kroupa, Pavel
ABSTRACT: Recent observations of the fields surrounding a few Milky Way-like galaxies in the local Universe have become deep enough to enable investigations of the predictions of the standard lambda cold dark matter (ΛCDM) cosmological model down to small scales outside the Local Group (LG). Motivated by an observed correlation between the number of dwarf satellites ( N sat ) and the bulge-to-total baryonic mass ratios ( B / T ) of the three main galaxies in the LG, i.e. the Milky Way, Andromeda, and Triangulum (M33), we use published data of three well-studied galaxies outside the LG, namely M81, Centaurus A, and M101, and their confirmed satellites, and we find a strong and significant correlation between N sat and B / T . This presents itself in contradiction with the hitherto published results from cosmological simulations reporting an absence of a correlation between N sat and B / T in the ΛCDM model. We conclude that, based on the current data, the N sat versus B / T correlation is no longer a property confined to only the LG.